A Companion to the Literature and Culture of the American South. - Gray, Richard (Blackwell companions to literature and culture., 2007)
From slave narratives to the Civil War, and from country music to Southern sport, this Companion is the definitive guide to the literature and culture of the American South. Consisting of over 30 original contributions, each of them written by an acknowledged authority in their field, the Companion reveals the diversity of the Southern region, as expressed in different forms of thought, work, and imaginative play. The first major section, concentrating on themes and issues, looks at the distinctive cultural characteristics of the American South and includes discussion of the visual arts, music.